Konsep Kognitif Padusi Entrepreneur Pengusaha Kue Sangkos - Atikah Ramadhini; Yanladila Yeltas Putra (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
Cognitive psychology is the study of how the brain processes information, it is related to the way we receive information from the outside world, how we understand that information and what its use is. The purpose of this study is also to find out the cognitive concepts that sangko cake entrepreneurs have. This study uses a phenomenological approach using an open-ended interview method to find out the facts of an event or the subject's opinion in depth conducted to two sangko cake entrepreneurs. The data analysis used in this study is a qualitative data analysis technique with the stages of data reduction, data presentation, and conclusion drawn. Testing the validity of the data using triagulation with other researchers in coding. The results of the study found 3 major themes with 15 themes. The results of this study were obtained that the research subject described the existence of women's cognitive concepts that are useful in entrepreneurial activities. Concepts that describe the existence of cognition consist of the subject of remembering, understanding, applying, analyzing, evaluating and creating products in entrepreneurial activities